Factors That Influence Purchase Decisions, Product Display, Price, And Promotion (Literature Review of Marketing Management) - Alya Abiyah Surya; Winda Zylvi Faradilla; Alyaa Jacynda; Naura Shadiqah Wibowo; Sabrina Nuraeni; Ni Nyoman Sawitri (International Journal of Economics Accounting and Management, 2024)
This study examines the factors that influence consumer purchasing decisions in the retail sector, focusing on product display, price, and promotion. In an era of increasingly competitive business, companies need to develop effective marketing strategies to attract consumer interest. Through a literature review, this study shows that attractive product displays can increase purchasing interest, while competitive prices and appropriate promotional strategies, such as discounts and cashback, play an important role in influencing purchasing decisions. Although many studies show a positive relationship between price and purchasing decisions, there is variation in its influence which emphasizes the need for further research. The results of this study are expected to provide new insights for retail business actors in formulating more relevant and effective marketing strategies, as well as increasing competitiveness in a competitive market